Effect of Gadolinium Content on the Corrosion Behavior of Magnesium Alloys in 1 wt.% NaCl Solution - Zidane,N. (2015)
The aim of this work was to study the effect of gadolinium content on the corrosion behavior of magnesium alloys in 1 wt.% NaCl solution at 21.5 (±0.5) °C. Four Mg-Gd alloys, namely Mg-2 wt.% Gd, Mg-5 wt.% Gd, Mg-10 wt.% Gd, and Mg-15 wt.% Gd, were studied. Weight loss measurements, potentiodynamic tests, electrochemical impedance spectroscopy, XR diffraction, and scanning electron microscopy combined with energy-dispersive X-ray spectroscopy (SEM-EDS) were performed on the four Mg-Gd samples. The results showed the influence of the Gd content on the corrosion behavior of these alloys in 1wt.% NaCl solution. The corrosion resistance of the Mg-Gd alloys was improved with the introduction of 10 wt.% Gd in Mg matrix. Thus, weight loss and electrochemical measurements revealed the better corrosion resistance for Mg10 wt.% Gd alloy. Further addition of Gd exceeding 10 wt.% in a magnesium matrix reduces the corrosion resistance of Mg-alloy and induces an incremental increase in the corrosion rate.